The Path to Innovation: The Antecedent Perspective of Intellectual Capital and Organizational Character - Li, Jingyi; Yu, Dengke (Frontiers in Psychology, 2018)
Purpose - The high-speed growth of China’s large-scale new economy indicates that innovation has become the most important economic growth pole. The purpose of this paper is to explore the structure and antecedents of the path to innovation, in which we focus on revealing the mediating effect of organizational character. Design/methodology/approach - Considering the indigenous context of China’s new economy, our research divides the innovation into two types: technological innovation and business model innovation. Then, we build a path model to achieve innovation by taking intellectual capital and organizational character as antecedents. Finally, we use structural equation method to measure the path model on the basis of sample data collected by a questionnaire survey. Findings - The results indicate that intellectual capital has a significant positive direct effect on technological innovation, while its direct effect on business model innovation is not significant. As for indirect effects, organization character not only mediate the beneficial effect of intellectual capital on technological innovation, but also mediate the beneficial effect of intellectual capital on business model innovation. In addition, technological innovation is positively affecting business model innovation, and it plays an intermediary role in the path of intellectual capital to business model innovation. Originality/value - This study takes intellectual capital and organizational character as the common antecedents of innovation and breaks down the content of innovation research into technological innovation and business model innovation. Thus, it has established a brand new theoretical analysis framework of dual innovation and enriched the innovation theory. This theoretical framework has important explanatory power for revealing the technological innovation and business model innovation activities carried out by a large number of corporate organizations in the context of China's new economy and the resulting economic boom. Furthermore, it would enlighten new economic organizations to organize innovation activities more effectively and achieve better innovation performance.